Reports of self-perception and oral health care of the institutionalized elderly person (Research, Society and Development, 2022)
The research aimed to understand the knowledge, customs and self-perception of the oral health of the elderly in a Long-Term Institution (LTI), in order to determine how this history influences the oral health of the institutionalized elderly. For this, a qualitative study was carried out, configured as an intervention research, composed of reports from residents of the LTI; and who investigated, through semi-structured interviews, their previous knowledge and oral health habits. The interviews were recorded, transcribed and analyzed. Six elderly people were interviewed and, from the content analysis, five main categories emerged: all participants were born in the south of Minas Gerais, have incomplete schooling and childhood marked by unsatisfactory oral health care. All reported occasional oral health care that became erratic in old age. Most participants took shelter voluntarily at the LTI, reporting a significant change in routine and loss of autonomy and independence. For the interviewees, the meaning of oral health is understood between satisfactory function, absence of diseases and they do not consider their own condition to be satisfactory. Therefore, although the reports present heterogeneous life trajectories, the experiences of aging and living in the LTI are similar. Oral health experiences are even more similar, with irregular hygiene habits, use of dentures and lack of interest in oral conditions. The reports were extremely important to understand the conditions and needs of the elderly and, from there, to build new paths for oral health education, going beyond the absence of diseases and considering the quality of life.